ANALISIS KESEDIAAN MEMBAYAR (WILLINGNESS TO PAY) DAN FAKTOR YANG MEMPENGARUHI PEMBELIAN TELUR OMEGA (STUDI KASUS PADA SUPERINDO GALUNGGUNG KOTA MALANG) - Mahardika, Arya Duta Kresna (Agridevina : Berkala Ilmiah Agribisnis, 2024)
The development of the Omega egg market in Indonesia, particularly in Malang City, has gained significant attention due to its potential health benefits. This study aimed to analyze consumer segmentation, determine their Willingness to Pay (WTP), and identify factors influencing their purchasing decisions for Omega eggs. A total of 70 respondents were surveyed, and their willingness to pay was evaluated. Using the Contingent Valuation Method (CVM), this study first establishes a hypothetical market scenario that provides consumers with information about the characteristics and benefits of omega-3 eggs. Bidding games are employed to determine the WTP values for the consumers. Subsequently, the average WTP for omega-3 eggs is calculated based on the collected data, allowing for the construction of a WTP curve. The results indicated that income (T-count < 0.05 (0.007)), distance (T-count < 0.05 (0.000)), time period (T-count < 0.05 (0.002), and knowledge (T-count < 0.05 (0.000) has significant effect on Willingness to Pay among omega egg buyers meanwhile lifestyle (T-count > 0.05 (0.076)) has no significant effect on Willingness to Pay among omega egg buyers. This research provides valuable insights for Omega egg producers, marketers, and policymakers. It highlights the importance of understanding consumer preferences and offers guidance on pricing and marketing strategies. Additionally, it emphasizes the potential for sustainable growth in the Omega egg industry. These findings can be instrumental in the development of policies and initiatives to promote healthier dietary choices in Indonesia.